AGILE DEVELOPMENT IMPLEMENTATION ON VIDYAMEDIC HEALTHCARE INFORMATION SYSTEM BASED ON SCRUM FRAMEWORK - Isep Lupti Nur; Mohammad Riza Nurtam; Daniel Nugraha (J-Icon : Jurnal Komputer dan Informatika, 2025)
Efficient and integrated information systems are essential for managing healthcare services, including patient data, laboratory results, and radiology records. This study presents the development of Vidyamedic, a web-based healthcare information system designed to streamline healthcare data management. The system was developed using HTML, CSS, and JavaScript for the front end and PHP with the Laravel framework for the back end. The development process adopted the Scrum framework, an Agile methodology that supports iterative and adaptive system development. The project was completed over eight weeks, divided into four sprints. Each sprint spanned two weeks or 10 working days. A total of 14 development tasks were completed by a team of four members. Key Scrum activities included product backlog creation, sprint planning, and the use of burndown charts to monitor progress and identify performance trends during development. System validation was conducted through black-box testing to ensure that each feature operated according to user requirements, without evaluating the system's internal structure. The resulting application provided role-based dashboards tailored for physicians, laboratory administrators, radiology administrators, and queue administrators. The findings demonstrate that Agile methodologies, particularly Scrum, can be effectively applied in the healthcare sector to develop reliable and adaptable information systems that improve healthcare data management.